2013
DOI: 10.1080/10410236.2013.814079
|View full text |Cite
|
Sign up to set email alerts
|

(De)stigmatizing the Silent Epidemic: Representations of Hearing Loss in Entertainment Television

Abstract: The number of adolescents, young adults, and senior citizens experiencing hearing loss has significantly increased over the last 30 years. Despite this prevalence, hearing loss receives little attention in popular and political discourse, except in its connection to aging. Thus, hearing loss and the use of hearing aids have been stigmatized, discouraging adults from seeking hearing evaluation and screening, and justifying the lack of insurance coverage for hearing devices. This research explored how and why he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 26 publications
1
23
0
1
Order By: Relevance
“…All of them reported that concealing the hearing difficulties (e.g., pretending to hear what was being said, refraining from making explicit demands that might help facilitate communication, choosing not to wear hearing aids) was the most common stigmatic behavior endorsed by elderly persons with hearing problems. Other common stigmatic behaviors found included denial and distancing oneself from communicative interactions (Foss, 2014;Southall et al, 2010). Consequences of stigma.…”
Section: Conceptual Issuesmentioning
confidence: 99%
“…All of them reported that concealing the hearing difficulties (e.g., pretending to hear what was being said, refraining from making explicit demands that might help facilitate communication, choosing not to wear hearing aids) was the most common stigmatic behavior endorsed by elderly persons with hearing problems. Other common stigmatic behaviors found included denial and distancing oneself from communicative interactions (Foss, 2014;Southall et al, 2010). Consequences of stigma.…”
Section: Conceptual Issuesmentioning
confidence: 99%
“…Görünmez', 'İşitme cihazı kullanıcıları için cihazın fark edilmemesi çok önemli olduğu için, .... 'ın yeni dome'ları soluk renkli tasarlanmıştır. Bu sayede kulak kanalının içinde neredeyse gözden kaybolurlar ve ancak çok dikkatle bakıldığında dışarıdan görülürler', '..... hep güçlü, hep gizli' Foss, [34] işitme engelli veya işitme kaybıyla ilişkili karakterlerin olduğu veya bu konunun geçtiği televizyon dizilerini incelemiştir. İşitme kaybının konu olduğu televizyon dizilerine fazla rastlanmamaktadır.…”
Section: Tablounclassified
“…In 2009, Foss noted that competing discourses about deafness can exist in a single media program, as exemplified with CSI: Crime Scene Investigation (CSI), with Gil Grissom's hearing loss, juxtaposed with positive representations of Deaf culture. More recently, Foss (2014) found that entertainment television rarely portrays the hearing loss experience, although d/Deaf characters frequently appear. The current study builds on this existing research to explore how fictional television depicts deafness and Deaf culture since 1987.…”
Section: Introductionmentioning
confidence: 98%